A Case of Negative Externality: Use of Pesticide and Its Impact on Health Among Farmers in Salumbhu Village, Nepal. (June 2021) - Rahman, Mohammad Mashiur; Chowdhury, Soumi Roy; K. Bohara, Alok; Karmacharya, Biraj
The widespread and uncontrolled use of harmful pesticide to facilitate mass-level agricultural production creates negative externalities ranging from environmental degradation to having adverse health implications to the users. This article explores a primary village-level data of farmers in the Salumbhu village of Nepal to investigate the health effects associated with pesticide use. A total of six health symptoms grouped into two categories such as serious health-related issues and irritants are analysed separately using ordered logit model. For the robustness of the results, Poisson and negative binomial models are also used. We found that farmers as compared to the non-farmers are significantly more prone to facing serious health issues. Furthermore, as farmers are the applicators of pesticide, the odds of them facing all the health symptoms increases significantly. The results are uniform across different measures of health and over multiple models, which advocates the need of appropiate regulations in the usage of pesticide in Nepal.